Jatung Utang Sebagai Pengiring Tari Hudog Pada Masyarakat Suku Dayak Kenyah di Desa Sungai Payang Kecamatan Loa Kulu Kabupaten Kutai Kartanegara Kalimantan Timur - Indah Pribadi Wulandari (SELONDING, 2017)
Jatung Debang is a traditional musical instrument of Dayak Kenyah tribe in Kalimantan archipelago. Made of elliptical wood and included in the category of Xylophone instrument. How to play Jatung debt is quite simple: hit with 2 separate logs for each slab of wood, each slab of wood tied to a rope that is mounted on a wooden block that is structured and will issue a key different tone. Jatung Debt itself is usually used as a ritual and dance accompanist Dayak Kenyah tribe.This study aims to determine the structure of the music jatung Debt as accompaniment Hudoq Community Dayak Kenyah tribe in the village of River Payang District of Loa Kulu Kutai regency and to determine the function of music jatung Debt accompaniment Hudoq Community Dayak Kenyah tribe in the village of River Payang District of Loa Kulu Regency of Kutai Kartanegara, using qualitative method. Music jatung debt as a dance accompanist hudog in lamin lung anai payang river village used to an expression of gratitude to the creator which is held after every harvest and to start growing rice again. Keywords: Jatung Utang music, Hudoq, in Sungai Payang Village